Characterization of thermoluminescence of chip cards for emergency dosimetry. (June 2020) - Kim, Hyoungtaek; Kim, Min Chae; Lee, Jungil; Discher, Michael; Woda, Clemens; Lim, Sangyeob; Chang, Insu; Lee, Seung Kyu; Kim, Jang-Lyul; Chung, Kisoo
Abstract: The thermoluminescence of different chip cards was measured and analyzed for emergency dosimetry. Three SIM cards that are commonly found in mobile communication providers in South Korea and three smart IC cards that can be purchased online were used for the experiment. Chemical element analysis based on EDS mapping images was carried out and different weight percent of silica was found for each chip card. Glow curves of radiation induced signals through different combinations of optical filters showed blue or red emissions depending on chip cards. Sensitivity change resulting from the thermal stimulation was found to be 1.8 ± 0.27 and 0.5 ± 0.06 for the blue and red emission, respectively. In addition, signal fading resulted in more than 20% of the initial signal remaining 20 days after irradiation, when the 100–150 °C signal is used. Furthermore, the dose response was recorded from 50 mGy to 10 Gy for each chip card. Highlights: Different model of chip cards were investigated for emergency dosimetry. Different weight percent of silica was found depending on chip cards. Blue or red emissions was measured depending on chip cards through different combinations of optical filters.